Policy change in China: the effects on the bamboo sector in Anji county - Ruíz Pérez, M.; Fu Maoyi; Xie Jinzhong; Belcher, B.; Zhong Maogong; Xie Chen (1996)
China has undertaken major economic policy changes since 1978, having moved from a plan economy to a predominantly market economy. These changes had great impact in the forestry sector. This paper aims to document these changes in the case of bamboo, and at the same time show bamboo's contribution to rural development in the new policy and economic conditions. New challenges will have to be met, such as diversification, improvement in a, uality, and standard and quality controls. The implementation of the policy changes is seen in a positive light, having avoided major disruptions in the economy. The case study of bamboo in Anji County also confirms the reduced influence of the State on production and consumption behaviour in the presence of a market system.